Multi-modality imaging for pre-procedural planning of transcatheter mitral valve interventions. (26th April 2023) - Tarzia, Pierpaolo; Ciampi, Pellegrino; Lanza, Oreste; Canali, Emanuele; Canestrelli, Stefano; Calò, Leonardo
Abstract: Transcatheter mitral valve interventions (TMVI), either repair or replacement, are established alternative options for patients with mitral regurgitation (MR) deemed not suitable for conventional open-heart surgery. Multi-modality imaging plays a pivotal role in the selection of patients, gaining insights into the anatomy of the mitral valve the mechanism and the severity of MR, which are essential to predict the success of these procedures. The aim of this review is to provide an overview on the role of multi-modality imaging in the patient selection and pre-procedural planning of TMVI.